Recent urbanization in China is correlated with a Westernized microbiome encoding increased virulence and antibiotic resistance genes - Winglee, Kathryn; Howard, Annie Green; Sha, Wei; Gharaibeh, Raad Z.; Liu, Jiawu; Jin, Donghui; Fodor, Anthony A.; Gordon-Larsen, Penny (Microbiome, 2017)
Urbanization is associated with an increased risk for a number of diseases, including obesity, diabetes, and cancer, which all also show associations with the microbiome. While microbial community composition has been shown to vary across continents and in traditional versus Westernized societies, few studies have examined urban-rural differences in neighboring communities within a single country undergoing rapid urbanization. In this study, we compared the gut microbiome, plasma metabolome, dietary habits, and health biomarkers of rural and urban people from a single Chinese province. We identified significant differences in the microbiota and microbiota-related plasma metabolites in rural versus recently urban subjects from the Hunan province of China. Microbes with higher relative abundance in Chinese urban samples have been associated with disease in other studies and were substantially more prevalent in the Human Microbiome Project cohort of American subjects. Furthermore, using whole metagenome sequencing, we found that urbanization was associated with a loss of microbial diversity and changes in the relative abundances of Viruses, Archaea, and Bacteria. Gene diversity, however, increased with urbanization, along with the proportion of reads associated with antibiotic resistance and virulence, which were strongly correlated with the presence of Escherichia and Shigella. Our data suggest that urbanization has produced convergent evolution of the gut microbial composition in American and urban Chinese populations, resulting in similar compositional patterns of abundant microbes through similar lifestyles on different continents, including a loss of potentially beneficial bacteria and an increase in potentially harmful genes via increased relative abundance of Escherichia and Shigella.